Significance of eosinophils in diagnosing Hashimoto′s thyroiditis on fine-needle aspiration cytology - Ekambaram Maheswari; Kumar Bipin; Chowdhary Nitlotpal; Siddaraju N; Kumar Surendra (Wolters Kluwer Medknow Publications, 2010)
Background: Hashimoto′s thyroiditis (HT) is the most common cause of hypothyroidism in those areas of the world where iodine levels are sufficient. Fine-needle aspiration cytology (FNAC) can accurately diagnose this lesion in most of the patients. However, a small percentage of cases may be missed due to inherent limitations of this procedure. Therefore, cytologic clues to increase sensitivity of diagnosis need to be searched for. Aims: To assess whether an eosinophilic infiltration of the thyroid gland has a higher association with HT than colloid goiter. Materials and Methods: The study was a case-control study. Smears obtained by FNAC of 50 case, each of HT (which served as cases) and colloid goiter (which served as controls) were observed. The number of eosinophils and neutrophils per high-power field (HPF) was counted in all the smears. The eosinophil-neutrophil ratio in the smears, diagnosed as HT, was then compared with that of colloid goiter using unpaired t-test. Results: Smears diagnosed as HT was found to have a significantly higher eosinophil-neutrophil ratio than smears diagnosed as colloid goiter (P value 0.0001). Conclusion: Eosinophilic infiltration of the thyroid gland has higher association with Hashimoto thyroiditis.